Photovoice and refugee research: The case for a 'layers' versus 'labels' approach to vulnerability. (October 2019) - Humpage, Louise; Fozdar, Farida; Marlowe, Jay; Hartley, Lisa
'Vulnerability' is a key concept used to understand the ethical implications of conducting refugee-focused research. This case study illustrates the need to follow Luna's (2009) call for a shift from a 'labels' to a 'layers' approach to vulnerability by analysing how two university ethics committees responded to issues of informed consent in two similar refugee research projects using the PhotoVoice method. The following commentary argues that, when driven by a research governance regime, ethics review risks viewing refugees through a static label of vulnerability, negatively affecting research viability and data quality. In contrast, a layers approach opens space for understanding the potential for vulnerability amongst refugee research participants while supporting PhotoVoice's goals of empowerment and facilitating agency. The case study highlights the need for national-level ethics statements that encourage a more flexible approach within research institutions.